HUBUNGAN PEMBERIAN ASI EKSKLUSIF TERHADAP BERAT DAN TINGGI BADAN BERDASARKAN UMUR BAYI DI DESA SIANTARASA, KABUPATEN TOBA, SUMATERA UTARA - Aritonang, Putri; Hutabarat, Theresia Saurina Febriadella; Silaen, Wesri Martua; Nasution, Wahyu Hadiyansyah; Pulungan , Ahmad Shafwan S. (PUSAT SAINS INDONESIA, 2025)
This study aimed to analyze the relationship between exclusive breastfeeding and infant growth in weight and height by age in Siantarasa Village, Toba Regency. The study was conducted using a quantitative approach on 30 infants aged 0–5 months at the Anggur Integrated Health Post (Posyandu), Nassau Community Health Center (Puskesmas), using weight measurements with infant scales, height measurements with a stadiometer, and collecting information on breastfeeding status, maternal awareness, and other supporting factors. The results showed that the average weight of female infants was 3.346 kg with a height of 91.473 cm, while male infants had an average weight of 3.34 kg and a height of 93.78 cm. The number of infants receiving exclusive breastfeeding decreased from 30 infants at 0 months of age to 26 infants at 2–5 months of age. The discussion of this study highlights the importance of exclusive breastfeeding in supporting infant growth through complete and easily absorbed nutritional content, such as calcium and protein, which strongly support the energy needs and development of infants. However, challenges were found in the form of a lack of maternal awareness, minimal support from health workers, and aggressive formula promotion, which impacted the reduced sustainability of exclusive breastfeeding. This study concludes that exclusive breastfeeding has a positive influence on infant growth in weight and height, and emphasizes the need for increased awareness and support from the community and health workers to ensure that exclusive breastfeeding practices can be maintained optimally.